Revival of “inward-oriented development”? The economic policy stance of the church in Latin America - Franz Peter Lang (Intereconomics, 1985)
Criticism within the Catholic churches of Latin America of the IMF and its approach to the development problems of the sub-continent has been persistently increasing in recent years. The measures imposed by the IMF, especially those following the payments crisis of 1982 have met with growing opposition. The impression that the churches have adopted a Marxist line on this issue is, however, a superficial one which needs to be examined more closely in the context of the dependencia theory and of recent economic developments in Latin America.
Keywords: 330; Development Theory